IMSTeP : Indonesian Marine Science And Techno Park Implementasi Kebijakan Model Van Meter Dan Van Horn Di Indonesia - Riki Kurniawan; M. Benny Alexandri; Heru Nurasa (Responsive: Jurnal Pemikiran Dan Penelitian Administrasi, Sosial, Humaniora Dan Kebijakan Publik, 2018)
Abstract The marine resources are waiting for the nation's explorer. Government support and past glory should be a giant step to develop real marine sector support programs. The nations assets supporting facilities and infrastructure of maritime science and technology sector is important to be considered for the efficiency of cost and expenditure of state and the progress of science and technology in the field of Marine.Pra feasibility that has been done, after the formation of Team Work  and the support from  central government collaboration across Ministries and Research Institutions, also supported by government readiness areas within the development of the Indonesia Marine Science and Technology Center (IMSTeP) should be a solid and well-maintained cooperation. The policy issued by the government is required to be able to cover every progress. However whether the policy can be implemented well operationally and substansinya or still need support derivative policies or other bureaucratic obstacles that need to be anticipated to accelerate the progress of this national program so that we soon become Master in his own country in the inner sector in particular ,,,, JalesvevaJayamahe. Abstrak Sumberdaya kelautan yang berlimpah menunggu para explorer anak bangsa untuk bergerak. Dukungan Pemerintah dan kejayaan masa lalu seharusnya menjadi cermin untuk mengembangkan program riil pendukung sektor kelautan khususnya. Aset pendukung sarana dan prasarana iptek sektor kelautan penting untuk diperhatikan demi efisiensi cost dan pengeluaran negara serta kemajuan Iptek di bidang Kelautan.Pra feasibility yang sudah dilakukan, setelah pembentukan Tim Pokja serta dukungan kolaborasi pemerintah pusat lintas Kementerian dan Lembaga Penelitian, di dukung oleh kesiapan pemerintah daerah didalam pengembangan Pusat Iptek Kelautan (IMSTeP) harus menjadi satu kerjasama yang solid dan terpelihara. Kebijakan yang dikeluarkan pemerintah dituntut mampu memayungi setiap progress kemajuannya.Namun apakah kebijakan tersebut dapat terimplementasikan dengan baik secara operasional dan substansinya atau masih perlukah dukungan kebijakan turunannya atau kendala birokrasi lain yang perlu segera di antisipasi untuk mempercepat progress progam nasional ini sehingga dengan segera kita menjadi Tuan di Negeri Sendiri di sektor keluatan khususnya,,,, JalesvevaJayamahe.